Modelling changes of aerosol compositions over Belgium and Europe. (14th February 2008) - Deutsch, Felix; Janssen, Liliane; Vankerkom, Jean; Lefebre, Filip; Mensink, Clemens; Fierens, Frans; Dumont, Gerwin; Roekens, Edward
Seasonal changes in aerosol compositions over Belgium and Europe are simulated with an extended version of the EUROS model. EUROS is capable of modelling mass and chemical composition of aerosols in two size fractions (PM2.5 and PM10-2.5). The chemical composition is expressed in terms of seven components: ammonium, nitrate, sulphate, primary inorganic compounds, elementary carbon, primary organic compounds and Secondary Organic Compounds (SOA). A comparison of modelled and measured aerosol concentrations showed that modelled concentrations are generally consistent with observed concentrations. The chemical composition of the aerosol showed a strong dependence on the season. High aerosol concentrations during the summer were mainly due to high concentrations of the secondary components nitrate, ammonium, sulphate and SOA in the size fraction PM2.5. In contrast, during autumn and winter, increased PM-concentrations were mainly due to higher concentrations of primary components, especially in the size fraction PM10-2.5.